DENTAL AND ORAL HEALTH EDUCATION FOR THE ELDERLY WITH SYSTEMIC CONDITIONS - Swastirani, Astika; Hidayat, Lukman Hakim; Majid, Nabil Naila; Aisy, Syakira Rahadatul; Turyono, Khalisah Raihana; Annisa, Iftah Mafaza; Laura, Christabel; Anggraeni, Alyaa Banafsya Salsabila (Caring: Jurnal Pengabdian Masyarakat, 2025)
Dental and oral health issues among the elderly are a significant concern as they greatly impact quality of life. This study aims to evaluate the effectiveness of a community service program in improving knowledge and awareness of dental and oral health among the elderly in Dieng Village, Klojen District, Malang City. The program was conducted by the Faculty of Dentistry, Brawijaya University (FKG UB). The methods used included an initial survey, health education, dental examination and treatment, as well as evaluation using pre- and post-tests. A total of 49 elderly individuals participated in the program, with 71% being female. Analysis results showed a significant increase in knowledge scores from the pre-test (M=10.98, SD=4.29) to the post-test (M=14.12, SD=5.19) with a p-value of 0.000. There was a significant difference based on gender, where females showed better results in the pre-test (M=11.97) and post-test (M=15.23) compared to males. Age was not found to have a significant influence on learning outcomes. The program successfully increased dental care awareness, with 80% of participants reporting improved tooth-brushing habits and a 30% reduction in active caries cases. These results indicate that the community service program effectively enhances knowledge and awareness of dental and oral health among the elderly.